2019
DOI: 10.1007/s00384-019-03476-y
|View full text |Cite
|
Sign up to set email alerts
|

Elderly-onset Crohn’s disease remarkably responsive to ustekinumab: a case report

Abstract: Background Crohn's disease is intractable and is frequently diagnosed in younger people. No clear policies exist regarding medical treatment for seniors with this disease, and its diagnosis and treatment are often hindered by difficulties attributable to comorbidities, complex differential diagnoses, and polypharmacy. We describe an elderly-onset Crohn's disease patient showing a marked remission-maintaining effect with no adverse events after administration of ustekinumab. Methods and results A 75-year-old pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Cheng et al [26] found that antitumor necrosis factor medication therapy did not bring about more increased risk of adverse events in old UC patients aged 60 years and over, including severe infections, hospitalization, or death. Also, recent studies have reported that new biological agents have satisfied effectiveness and safety in the treatment of elderly UC, such as vedolizumab or ustekinumab [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [26] found that antitumor necrosis factor medication therapy did not bring about more increased risk of adverse events in old UC patients aged 60 years and over, including severe infections, hospitalization, or death. Also, recent studies have reported that new biological agents have satisfied effectiveness and safety in the treatment of elderly UC, such as vedolizumab or ustekinumab [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The median age of onset in the elderly and nonelderly was also significantly different (62 [58-66] vss. 29 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], p < 0.001). As shown in Table 1, at the first admission, dis-ease duration was similar around 3 years in these 2 groups.…”
Section: Baseline Characteristicsmentioning
confidence: 99%